Rationality Analysis of Antibiotics for Community-Acquired Pneumonia in Adult Inpatients at X Hospital Sukoharjo - Rahardjoputro, Rolando; Amrullah, Adhi W.; Rizky, Wahyu; Ernawati, Ernawati; Wahyudi, Andrey; Widyaningrum, Nova R. (Universitas Padjadjaran, Indonesia, 2025)
Community-acquired pneumonia in adult patients contributes to high morbidity and mortality rates. The rationality of antibiotics for community-acquired pneumonia pharmacotherapy can determine the result of patient clinical outcomes. The aim of this study was to determine antibiotics rationality for community-acquired pneumonia in adult inpatients at X Hospital Sukoharjo and relationship between antibiotics rationality and its clinical outcomes.This study was analytical cohort design with retrospective data in the form of patient medical records for the period 2022. Sampling method was carried out using total sampling with inclusion criteria being patients aged ≥ 18 years, male or female, diagnosed with community-acquired pneumonia and receiving antibiotic therapy. The total samples was 102 who met the inclusion criteria which 52% was female gender and predominantly aged ≥ 65. The rationality analysis using Gyssens method showed that 29.51% of antibiotics were given rationally with the highest number of irrationalities due to another more effective antibiotics (category IVA) at 54.90%. There was no significant relationship between antibiotic rationality and its clinical outcomes.